36 Higher serum vitamin D levels are associated with higher physical health-related quality of life in high-risk, older adults following non-st elevation acute coronary syndrome undergoing invasive care. (17th July 2020) - Beska, Benjamin; Neely, Dermot; Kunadian, Vijay
Abstract : Introduction: A large proportion of older patients with cardiovascular disease have low serum vitamin D levels. Such deficiency states have been linked with lower health-related quality of life (HRQoL). The Improve Cardiovascular Outcomes in High Risk PatieNts (ICON-1) study (NCT01933581 ) has previously demonstrated that serum vitamin D levels do not predict major adverse cardiovascular events (MACE) at 1 year in high-risk older adults being managed invasively for non-ST elevation acute coronary syndrome (NSTEACS). However, the relationship between serum vitamin D levels and HRQoL in older patients with NSTEACS is unclear. This further analysis of the ICON-1 cohort aims to investigate the relationship between serum vitamin D and HRQoL in high-risk, older adults managed invasively for NSTEACS. Methods: Patients aged ≥75 years presenting with NSTEACS (n=293) were recruited to the multi-centre prospective cohort ICON-1 study. Baseline serum total vitamin D was measured by electrochemiluminescent immunoassay prior to coronary angiography, split into two groups by the median for analysis. HRQoL was assessed within 24 hours post-procedure using the Short Form 36 Health Survey (SF-36) (License Number QM033917), values reported as norm-based scores. At one-year follow-up SF-36 scores were repeated. SF-36 consists of 4 physical subscales, summarised as Physical Component Summary. Statistical differences between groups were assessed with Kruskal-Wallis testing. Multi-variate linear regression was used to probe the impact of serum vitamin D on HRQoL adjusted for the a priori co-variates of age and sex. Results: Mean age was 80.4±4.8 years (61.8% male). Baseline median vitamin D was 29.0 [IQR 16.0–53.0] nmol/L. Patients were split by the median baseline vitamin D: low serum vitamin D (n=147, median 16.0 [IQR 12.0–23.0] nmol/L) and high serum vitamin D (n=146, median 53.0 [IQR 40.0–75.0] nmol/L). Both at baseline and at 1 year, those with a high serum vitamin D had significant higher scores in physical functioning (P<0.0001 at baseline and P=0.002 at 1 year, respectively) and physical component score (P=0.002 at baseline and P=0.038 at 1 year) compared to those with a low serum vitamin D (Table 1 ). At baseline, there was a significant association between serum vitamin D and a higher physical functioning (β=0.15, P=0.028) and physical component scores (β=0.16, P=0.009), after adjustment for age and sex (Table 2 ). This association was also apparent at 1-year follow-up, with a significant adjusted association between serum vitamin D and physical functioning (β=0.21, P=0.003). Conclusions: There is an association, independent of age and sex, between serum vitamin D and physical health-related quality of life at both presentation and at 1-year follow-up after invasive management of NSTEACS in high-risk older adults. Although vitamin D deficiency has not been shown to predict MACE, it may play a plausible role in the significant morbidity experienced by older adults with cardiovascular disease. Conflict of Interest: None to declare